Navigating Stress in Higher Education: An Array of Intervention Strategies - Nurul Shuhada Sharif Mudin; Aslina Ahmad; Pau Kee (International Journal of Education, Information Technology, and Others, 2023)
Stress is a common and significant problem faced by students in higher education institutions, with negative consequences for academic performance, mental health, and overall well-being. This concept paper explores the importance of diverse interventions to help university students manage stress. The literature review provides a comprehensive overview of various types of interventions that have been used to address stress among university students, including mindfulness-based interventions, cognitive-behavioural interventions, physical exercise interventions, and social support interventions. The paper proposes a range of interventions that could be effective in addressing stress among university students, with a particular focus on those that are culturally sensitive, easily accessible, and tailored to meet the needs and preferences of diverse student populations. The conclusion summarises the main findings and recommendations, emphasising the importance of implementing diverse stress interventions to support the well-being and academic success of all university students.